PENGANGKATAN DEWAN KOMISARIS DAN DIREKSI BANK MENURUT UNDANG-UNDANG NOMOR 7 TAHUN 1992 JO. UNDANG-UNDANG NOMOR 10 TAHUN 1998 TENTANG PERBANKAN - Bismar Nasution; Windha Windha (TRANSPARENCY, 2014)
One of the efforts that can be made to produce a good management structure is via a selection process of the owner and board of management (the board of commissioners and board of directors) on all the banks that carried through to test the ability and propriety (fit and proper test). Appointment of board of commissioners and board of directors of the bank are regulated in the banking act. However, during this appointment of board of commissioners and board of directors of the bank comply with the "no" because there are several incomplete article and was deleted. The problems raised in this thesis is how the appointment of board of commissioners and board of directors of the bank according to the banking law, how the role of Bank Indonesia in the appointment of the board of commissioners and board of directors of the bank, and how the implementation of the regulation of board of commissioners and board of directors the adoption in a law of banking Research methods used in the writing of this thesis is that the normative legal research methods or ways of researching the existing library materials. The first phase of the normative legal research is research aimed at obtaining objective law (legal norms), which is conducting research on legal issues. The second phase of the normative legal research is research aimed at obtaining subjective laws (rights and obligations). Research used are descriptive and used qualitative approaches that aim to understand and grasp the symptoms are examined. Data collection tools include the study of librarianship, legislation, books, scientific papers, etc. The result of this research shows clearly that the appointment of the board of commissioners and board of directors in terms of banking law in practice is not usable because the rules on adoption does not exist. Bank Indonesia's role in the appointment of the board of commissioners and board of directors of the bank is as a regulator and supervisor of banks as mentioned in article 8 subparagraph c act– BI. The implementation of the appointment of the board of commissioners and board of directors of the bank in terms of the banking act in practice cannot be used because there was no appointment regulations.